Wideband acoustic immittance in children with Down syndrome: prediction of middle-ear dysfunction, conductive hearing loss and patent PE tubes. (2nd September 2017) - Hunter, Lisa L.; Keefe, Douglas H.; Feeney, M. Patrick; Brown, David K.; Meinzen-Derr, Jareen; Elsayed, Alaaeldin M.; Amann, Julia M.; Manickam, Vairavan; Fitzpatrick, Denis; Shott, Sally R.
Abstract: Objective : The purpose of this study was to evaluate pressurised wideband acoustic immittance (WAI) tests in children with Down syndrome (DS) and in typically developing children (TD) for prediction of conductive hearing loss (CHL) and patency of pressure equalising tubes (PETs). Design : Audiologic diagnosis was determined by audiometry in combination with distortion-product otoacoustic emissions, 0.226 kHz tympanometry and otoscopy. WAI results were compared for ears within diagnostic categories (Normal, CHL and PET) and between groups (TD and DS). Study sample : Children with DS ( n = 40; mean age 6.4 years), and TD children ( n = 48; mean age 5.1 years) were included. Results : Wideband absorbance was significantly lower at 1–4 kHz in ears with CHL compared to NH for both TD and DS groups. In ears with patent PETs, wideband absorbance and group delay (GD) were larger than in ears without PETs between 0.25 and 1.5 kHz. Wideband absorbance tests were performed similarly for prediction of CHL and patent PETs in TD and DS groups. Conclusions : Wideband absorbance and GD revealed specific patterns in both TD children and those with DS that can assist in detection of the presence of significant CHL, assess the patency of PETs, and provide frequency-specific information in the audiometric range.